AL-QUR’AN DAN DZIKIR : APAKAH EFEKTIF MENGATASI KECEMASAN KARENA COVID-19 SEBAGAI KONDISI PANDEMI? - Hidayat, Bahril; Rahman, Azhar Abdul; Nugroho, Sigit; Leybina, Anna V; Muliadi, Rahmad; Listyani, Nilla; Lubis, Layla Takhfa (Psikis : Jurnal Psikologi Islami, 2023)
The Covid-19 outbreak in addition to causing a health emergency also affects psychologically. This is because people are worried for their safety, which causes them to be more alert and suspicious. Excessive anxiety can be categorized as a mental disorder. The Al-Qur'an contains various components needed by mankind as guidelines for achieving prosperity in this world and the hereafter. Reading Qur'an and doing dhikr (dzikir) every day can reduce a person's anxiety level and provide continuous calm which turns out to be a very effective therapy for a person in dealing with life stressors. This research is trying to prove that the Qur'an and dhikr can be a strategy to overcome anxiety during Covid-19. This study employed a literature review research design with PRISMA analytical technique. The articles analyzed in this study were 13 articles. The results showed that the provision of therapy using the Al-Qur’an and dhikr gives a person peace, happiness, and security which can reduce anxiety level because of Covid-19. The results of this research are expected to become a reference for practitioners, researchers, and policy makers to use the Islamic therapy approach and other religious spiritual approach in line with the need of every country facing a pandemic, especially in Indonesia, Malaysia, and Russia.